Wheat and barley differently affect porcine intestinal microbiota1. (14th August 2015) - Weiss, Eva; Aumiller, Tobias; Spindler, Hanna K; Rosenfelder, Pia; Eklund, Meike; Witzig, Maren; Jørgensen, Henry; Bach Knudsen, Knud Erik; Mosenthin, Rainer
Abstract: BACKGROUND: Diet influences the porcine intestinal microbial ecosystem. Barrows were fitted with ileal T‐cannulas to compare short‐term effects of eight different wheat or barley genotypes and period‐to‐period effects on seven bacterial groups in ileal digesta and faeces by qPCR. RESULTS: Within genotypes of wheat and barley, there was no difference ( P  > 0.05) in contents of analysed NSP, yet cereal types differed ( P  < 0.001) except for soluble arabinoxylans. Genotypes showed no effect on bacterial gene copy numbers. In ileal digesta of barley‐ compared to wheat‐fed pigs, log10 copy numbers were lower ( P  < 0.05) for total eubacteria (9.6–9.8), Bacteroides–Prevotella–Porphyromonas (6.5–6.8), Clostridium cluster IV (6.7–6.9), and Roseburia spp. (6.6–7.2), while higher copy numbers were found for Lactobacillus spp. (9.4–8.8). Enterobacteriaceae (7.0–7.8) and Bifidobacterium spp. (7.0–7.7) were lower ( P  < 0.001) in faeces of barley compared to wheat‐fed pigs. Ileal eubacteria, Clostridium cluster IV and Roseburia spp. linearly increased from period 1 to 8 for both cereals ( P  < 0.05). CONCLUSION: Wheat and barley differently influence microbial composition particularly in the small intestine, with barley increasing the Lactobacillus spp.: Enterobacteriaceae ratio, underlining its potential to beneficially manipulate the intestinal microbial ecosystem. © 2015 Society of Chemical Industry